A heterozygous duplication variant of the HOXD13 gene caused synpolydactyly type 1 with variable expressivity in a Chinese family - Tahir Zaib; Wei Ji; Komal Saleem; Guangchen Nie; Chao Li; Lin Cao; Baijun Xu; Kexian Dong; Hanfei Yu; Xuguang Hao; Yan Xue; Shuhan Si; et al. (BMC, 2019)
Abstract Background Synpolydactyly type 1 (SPD1), also known as syndactyly type II, is an autosomal dominant limb deformity generally results in webbing of 3rd and 4th fingers, duplication of 4th or 5th toes. It is most commonly caused by mutation in HOXD13 gene. In this study, a five-generation Chinese family affected with SPD1 disease were collected. We tried to identify the pathogenic variations associated with SPD1 involved in the family. Methods We used the whole genome sequencing (WGS) to identify the pathogenic variant in this family which was later confirmed by PCR-Sanger sequencing. The genetic variation were evaluated with the frequencies in the 1000 Genome Project and Exome Aggregation Consortium (ExAC) dataset. The significance of variants were assessed using different mutation predictor softwares like Mutation Taster, PROVEAN and SIFT. The classification of variants was assessed according to American College of Medical Genetics and Genomics (ACMG) guidelines. Results Our results showed the mutation of 24-base pair duplication (c.183_206dupAGCGGCGGCTGCGGCGGCGGCGGC) in exon one of HOXD13 in heterozygous form which was predicted to result in eight extra alanine (A) residues in N-terminal domain of HOXD13 protein. The mutation was detected in all affected members of the family. Conclusion Based on our mutation analysis of variant c.183_206dupAGCGGCGGCTGCGGCGGCGGCGGC in HOXD13 and its cosegregation in all affected family members, we found this variant as likely pathogenic to this SPD1 family. Our study highlights variable expressivity of HOXD13 mutation. Our results also widen the spectrum of HOXD13 mutation responsible for SPD1.